Organisational Behaviour, Artificial Intelligence, Hybrid Work Patterns, and Perceptions of Fairness Towards Gen Z Job Satisfaction - Mauli Sarintan; Suhardi (Al-Qalam Institue, 2025)
This study aims to analyze the influence of organizational behavior, artificial intelligence (AI), and hybrid work patterns on job satisfaction among Generation Z (Gen Z) employees, with perceived justice as a moderating variable. The respondents in this research were Gen Z employees of Pangkalpinang City's local government who work in hybrid work systems and have interacted with AI-based technologies. The study employed a quantitative approach using an online survey, with data collected from 161 respondents. Data analysis was conducted using Partial Least Squares (PLS) in SmartPLS. The results indicate that organizational behavior and hybrid work patterns have positive, significant effects on job satisfaction and perceived justice. In contrast, AI has a significant impact on perceived justice but not on job satisfaction. Moreover, job satisfaction mediates the relationship between hybrid work patterns and perceived justice, suggesting that flexible work arrangements enhance both fairness perceptions and job satisfaction. These findings highlight the importance of balancing technological implementation, flexible work systems, and a fair organizational culture to improve Well-being and loyalty among Gen Z employees in the public sector.